MIFOLOGIK TAFAKKUR VA UNING EVOLUTSIYASI: XAOSDAN KOSMOS SARI ONGLI HARAKAT. - Sheraliyeva Muhabbat, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This  research  provides  an  extensive  academic  inquiry  into  the  essence  of mythological thinking and its intricate historical evolution across the timeline of human civilization.  The  study  posits  that  mythology  is  not  merely  a  collection  of  archaic fables,  but  a  primary  and  sophisticated  cognitive  framework  that  enabled  early humanity  to  interpret  existence,  institutionalize  social  hierarchies,  and  establish  a coherent cosmic order. By analyzing the structural transition from "mythos" to "logos," the  article  illuminates  the  evolutionary  trajectory  of  human  consciousness—from symbolic-metaphorical  perceptions  to  the  rigorous  domains  of  rational-logical reasoning. Furthermore, the findings demonstrate that mythological archetypes remain deeply  embedded  as  a  psychological  substrate  within  modern  cultural  constructs, shaping contemporary ideologies, art, and collective identity patterns.